Lambung Mangkurat University students' response to library services during the Covid-19 pandemic - Mariatul Qibthiyyah; Endang Ernawati (Jurnal Kajian Informasi dan Perpustakaan, 2022)
Student responses to ARCS (Attention, Relevance, Confidence, and Satisfaction) are related to describing the level of student attention to library services during the Covid-19 pandemic. It includes the relationship between the services provided and student needs (relevance), student confidence in receiving library services, and student satisfaction with library services during the pandemic. The study analyzes student responses based on ARCS to Universitas Lambung Mangkurat (ULM) library services during the Covid-19 pandemic. This study used a mixed-method design in the triangulation design: quantitative data model validation procedure. In this model, the researcher collected quantitative and qualitative data, then analyzed each of these data. The next stage was to carry out further analysis by validating the quantitative analysis results using qualitative results. The study was conducted in June-October 2020. The research sample was 500 students who visited the ULM library. Qualitative data were taken from 10 students using random sampling from the sample. The research instruments were validity sheets, questionnaires, and interview protocols. Specific findings in this study in detail were as follows: student responses based on attention, student responses based on relevance, student responses based on student confidence, and student responses based on satisfaction with ULM library services during the pandemic were in the category 'good'. Based on ARCS, this study concludes that student responses to ULM library services during the Covid-19 pandemic are good.